ОЦЕНИВАНИЕ УСЛОВНОЙ ФУНКЦИИ ВЫЖИВАНИЯ В СПЕЦИАЛЬНОЙ РЕГРЕССИОННОЙ МОДЕЛИ СЛУЧАЙНОГО ЦЕНЗУРИРОВАНИЯ С ДВУХ СТОРОН - Абдикаликов, Ф.; Бегжанова, К.; Сейтахов, Р. (SCIENCE and SOCIETY, 2024)
In the article constructs a semiparametric estimate of the conditional survival function in a special informative regression model of random censoring on both sides. The asymptotic properties of estimators are investigated.
Keywords: random censoring; informative model; nonparametrical regression; survival function; semiparametrical estimation